EVALUASI PERSEDIAAN OBAT COVID-19 PADA MASA PANDEMI DAN FAKTOR YANG MEMPENGARUHI DI RUMAH SAKIT PEMERINTAH DAN RUMAH SAKIT SWASTA DI KOTA MAKASSAR - Fadila Rizki; Erna Kristin; Ni Luh Putu Eka Putri Andayani (Journal of Health Service Management, 2023)
Background: Drug management realizes the availability of drugs needed to be effective and efficient, especially during the COVID-19 pandemic. The high use of COVID-19 drugs makes several types of drugs needed to experience vacancies, and due to changes in government regulations make some COVID-19 drugs stagnant.Objectives: To evaluate the supply of COVID-19 drugs during the pandemic and the factors that influence it in government and private hospitals in Makassar CityMethods: This study is a mixed-method study with a sequential explanatory design. Quantitative data were obtained retrospectively from January to December 2021 by searching drug management documents. Qualitative data was obtained through in-depth interviews with 12 informants.Results: The availability of COVID-19 drugs in government hospitals is 19.3 months, while in private hospitals, it is 13.6 months. Factors that affect drug supply are the method of planning drug needs, Lead Time, and several changes in guidelines.Conclusions: The supply of COVID-19 drugs is still excessive at that Public Hospital, and the factor that most influenced the supply of COVID-19 drugs was changes in guidelines.